MEMECYLON WAYANADENSE (MELASTOMATACEAE), A NEW SPECIES FROM THE WESTERN GHATS, INDIA - Sivu, A. R.; Narayanan, M. K. Ratheesh; Pradeep, N. S.; Kumar, N. Anil; Pandurangan, A. G. (Edinburgh Journal of Botany, 2012)
Memecylon wayanadense Ratheesh, Sivu & Pradeep, a new species of Melastomataceae from the Wayanad forests of Kerala, India, is described and illustrated. The new species is allied to Memecylon angustifolium, M. rivulare and M. sivadasanii but differs in habit, leaf shape, sclereid type, inflorescence type and position, and the shape and size of the sepals and petals. An UPGMA analysis of 20 RAPD primers resulted in two major clusters with Memecylon sivadasanii in one cluster and M. rivulare, M. angustifolium and M. wayanadense in the second cluster. Memecylon wayanadense forms a subgroup within the second cluster.